2020
DOI: 10.3390/en13236456
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Reservoir Fluids in the Aspect of CO2 Injection for Selected Oil Reservoirs in Poland

Abstract: Worldwide experiences related to geological CO2 storage show that the process of the injection of carbon dioxide into depleted oil reservoirs (CCS-EOR, Carbon Capture and Storage—Enhanced Oil Recovery) is highly profitable. The injection of CO2 will allow an increasing recovery factor (thus increasing CCS process profitability) and revitalize mature reservoirs, which may lead to oil spills due to pressure buildups. In Poland, such a solution has not yet been implemented in the industry. This work provides addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Since oilfield brines are usually strongly saline, the minerals present in them can be a valuable chemical resource [34]. The composition of reservoir brines is very diverse and complex, they contain dissolved and dispersed hydrocarbons, dissolved inorganic salts, dissolved gases and radionuclides [39,40]. Among the various elements, lithium is currently receiving the most attention due to the growing demand associated with electromobility.…”
Section: Volume Current Usage and Composition Of Oilfield Brinesmentioning
confidence: 99%
“…Since oilfield brines are usually strongly saline, the minerals present in them can be a valuable chemical resource [34]. The composition of reservoir brines is very diverse and complex, they contain dissolved and dispersed hydrocarbons, dissolved inorganic salts, dissolved gases and radionuclides [39,40]. Among the various elements, lithium is currently receiving the most attention due to the growing demand associated with electromobility.…”
Section: Volume Current Usage and Composition Of Oilfield Brinesmentioning
confidence: 99%
“…The authors of the work [71] found that for oil-CO 2 MMP is equal to 11.9 MPa and all other gases higher than 30 MPa. There may also be a lower MMP value, depending on the type of oil; for example, 8.3 MPa, as in the article [72].…”
Section: Increasing Oil Recovery By Carbon Dioxide Pumped Into the Reservoirmentioning
confidence: 99%